Penerapan Experiential Marketing - Kustini, Kustini (Jurnal Riset Ekonomi dan Bisnis, 2007)
In doing experiential marketing, bread boutique "Bread Talk" involves customer emotion in order to feel pleasure during they buy bread. With involving customer emotion in doing bread buying, so customer will get interesting experience during they buy product of Bread Talk. Interesting experience obtained by customer stimulate customer to be loyal. Purpose of this research to analyze influence experiential marketing against customer loyalty on bread boutique "Bread Talk" in Plaza Surabaya.Data used in this research is primary data obtained from respondent answer which come through questionnaire with interval measurement scale. The Respondents are buyers which buy bread in Bread Talk Plaza Surabaya more than 1 times. Sampling technique use incidental sampling with the number of respondent about 200 customers. Analytical technique use SEM which will better to see the causality which will be tested.Based on result of data processing, obtained that experiential marketing have positive effect toward customer loyalty in bread boutique Bread Talk. This thing mean if sense, feel, act and think from customer of bread boutique Bread Talk go up, so customer loyalty of Bread Talk go up too.Keywords: Experiential Marketing, Customer Loyalty